An efficient bionic topology optimization method for transversely isotropic materials. (15th November 2018) - Völkl, Harald; Klein, Daniel; Franz, Michael; Wartzack, Sandro
Abstract: Optimization specifically for fiber reinforced plastics (FRP) is becoming more and more important for creating high-quality composite structures. Yet, in spite of the increasing use of topology optimization (TO) within product development, specific TO methods for transversely isotropic materials like FRP are scarce in research and even more scarce in practical application. This is amongst other reasons caused by the challenge of simultaneous optimization of mutually dependent material distribution and fiber orientations, which poses an obstacle to established gradient-based optimization routines in terms of iterations (run time) and gradient formulation. Thus, based on bionic methods, an efficient, empirical optimization method is proposed to enable fast and FRP-suitable geometry propositions. Case studies show efficiency and effectiveness: the new approach offers very fast convergence; plus perceptible stiffness gains compared to established topology optimization for isotropic materials.